A rare case of extraovarian dysgerminoma in pregnancy - N., Sumathi; N., Rajasekaran P.; S., Valarmathy; V., Divya; Deivasikamani, Deenadayalan; ., Jayashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Extraovarian germ cell tumors are very rare and their occurrence in pregnancy is extremely rare. We presented a case of extraovarian dysgerminoma on the anterior abdominal wall in a G2P1L1, 34 weeks. It is challenging to manage such tumors, obstacles in the way namely are diagnosis as the presentation can be different from classical ovarian GCTs, limitations in the investigatory modalities in pregnancy, and management involving three independent entities-tumor, mother, fetus.